Participation of Urban Women in Agricultural Production Activities in the Sokoto Metropolis, Nigeria - Barau, A. A.; Oladeji, D. O. (JNRD - Journal of Natural Resources and Development, 2017)
This study examines the participation of urban women in agricultural production activities in the Sokoto metropolis, Nigeria. Both primary data and secondary information were used in the study. The primary data were obtained using a structured questionnaire, administered to 72 respondents selected using the snowball sampling technique. Descriptive and inferential statistics were used to analyze the primary data generated. These include frequency and percentage, and Pearson product moment correlation, respectively. The results show that most of the urban women (38.9 %) were in the active age range and had a family size of 1-5 persons (73.6 %). The majority attained tertiary education (62.5 %) and have relatively low income (61.1 %), with monthly earnings of 5,000-99,000 Naira. The majority of the women were involved in agricultural production activities all year round (52.8 %) with the highest participation seen in poultry farming (43.1 %). Although most of the women were motivated to participate for several reasons, it was mostly for the increased income (33.3 %). It was also found that the major constraint faced was inadequate capital (43.1 %). Age, marital status, educational attainment, household size and farm size were negatively and not significantly (p